Theoretical study of aromatic compounds with inhibitory activity of β-hematin formation (2006)
ABSTRACT: Malaria is the most important parasitic diseases, affecting almost half of the world. This disease increases in the population of Colombia each year. 5 aromatic compounds were sinthetized, they were evaluated as inhibitor of β-hematin formation and we reported the theoretical study of the compounds-hematin aggregated in order to determine how the interaction drug-receptor could be established. Theoretical study using Gaussian 03 shows the interaction between carbonyl oxygen and Fe in the porphyrin ring of hemin. The modification of funtional groups in the compounds changes the inhibition of compounds-hemin aggregated. The geometrical parameters of the complexes are relationed with the inhibitory activity.